Pola Komunikasi Masyarakat Aceh dalam Interaksi Lintas Budaya dengan Warga Negara Asing - Muhammad Yunus Ahmad; Muhammad Roja Erlian; Ridhwansyah Ridhwansyah (LaKaspia, 2025)
Interactions between Acehnese communities and foreign nationals have intensified alongside the growth of tourism, education, and social mobility in Aceh. Differences in language, cultural backgrounds, and social norms require adjustments in intercultural encounters. This study analyzes Acehnese communication patterns in interactions with foreign nationals, examines the socio-cultural factors that shape these patterns, and describes observable forms of communicative adaptation in everyday encounters. Employing a descriptive qualitative approach, the study draws on participant observation in Banda Aceh and Sabang, complemented by document-based review as a comparative analytical frame. Data were analyzed thematically through data reduction, display, and conclusion drawing. The findings indicate that Acehnese communication tends to emphasize politeness, caution, and indirect strategies in both verbal and nonverbal forms. These tendencies are reflected in careful wording, controlled intonation, and the management of interpersonal distance and eye contact, particularly in cross-gender interactions. Religious values, customary norms, and prior exposure to intercultural encounters accompany the formation of these patterns. Communicative adaptation is observed through simplified language use, strengthened nonverbal cues, and the selection of “safe” conversation topics. Overall, intercultural communication in Aceh emerges as an ongoing negotiation between openness to outsiders and the maintenance of local norms.